Experimental Study of Heat Transfer Parameters usin g internal threaded pipe fitted with inserts of different materials - Mr. Dhiraj D.Shinde; Prof. A.M.Patil; Mr. Sagar V. Jagtap (International Journal of Innovations in Engineering Research and Technology, 2021)
Many heat transfer enhanced techniques have simultaneously been developed for the improvement of energyconsumption, material saving, size reduction and pumping power reduction. Screw tape inserts in tubes are atypical technique that offers a higher heat transfer increaseand, at the same time, only a mild pressure droppenalty.